Penerapan Pendekatan ABCD (Asset Based Community Driven) dalam Pemberdayaan Ekonomi Perempuan - Rachmatsyah, T. Herry; Soemartono, Triyuni; Djatmika, Gatot Hery; Sukmana, Pandji (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to implement and evaluate the effectiveness of the Asset-Based Community Driven approach in empowering women economically within local communities. This approach positions community assets as the primary foundation for creating sustainable social and economic transformation. The project was implemented using a participatory, descriptive qualitative research design, divided into five main stages: community asset mapping, collective vision development, action planning, resource organization, and implementation and reflection. All stages actively involved women in the process of identifying strengths, developing business plans, and implementing economic activities based on local potential. Program results indicate a significant increase in women's awareness of their own and their community's potential, the emergence of new locally-based leadership, and increased economic capacity, including digital literacy and small business management skills. Furthermore, the program also resulted in the formation of a solidarity-based business network among women who support each other. These findings confirm that the ABCD approach is capable of promoting empowerment rooted in the internal strengths of the community, and not simply the transfer of knowledge or economic assistance. This approach is relevant for replication as an alternative model for more inclusive, sustainable, and gender-equitable development.